The role of welfare in family income inequality: 1968–2016. (December 2020) - Wagmiller, Robert L.; Lee, Kristen Schultz; Su, Jessica Houston
Highlights: Tax and in-kind benefits reduced inequality in the U.S. until the Great Recession. Redistributive effects of welfare income dropped in all states after welfare reform. Results show need for direct income transfer policies for most vulnerable families. Abstract: Income inequality among U.S. families with children has increased over recent decades, coinciding with a period of significant reforms in federal welfare policy. In the most recent reform eras, welfare benefits were significantly restructured and redistributed, which may have important implications for income inequality. Using data from the 1968–2016 March Supplement to the Current Population Survey (N = 1, 192, 244 families with children) merged with data from the historical Supplemental Poverty Measure, this study investigated how income inequality and, relatedly, the redistributive effects of welfare income and in-kind benefits changed, and whether such changes varied across states with different approaches to welfare policy. Results suggest that cash income from welfare became less effective at reducing income inequality after the 1996 welfare reform, because the share of income coming from cash welfare fell and was also less concentrated among the neediest families. At the same time, tax and in-kind benefits reduced inequality until the Great Recession. Consistent with the "race to the bottom" hypothesis, results suggest that the redistributive effects of welfare income dropped in all states regardless of their approach to welfare policy.